2012
DOI: 10.1002/jps.22822
|View full text |Cite
|
Sign up to set email alerts
|

On Quantitative Relationships Between Drug-Like Compound Lipophilicity and Plasma Free Fraction in Monkey and Human

Abstract: Drug interactions with plasma proteins influence their pharmacokinetics and pharmacodynamics. We aimed to test whether a strong quantitative relationship exists between plasma free fraction (fP) and lipophilicity for low molecular weight nonacidic drug-like compounds. We measured the n-octanol-buffer distribution coefficients at pH 7.4 (mlogD) of 18 diverse radiotracers (<470 Da) used for brain imaging with positron emission tomography in vivo. Lipophilicities were also computed as clogD with two software pack… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(72 citation statements)
references
References 43 publications
6
66
0
Order By: Relevance
“…The octanol/aqueous buffer partition coefficients (log P 7.4 ) of [ 18 F] 26 - [ 18 F] 29 (Table 2) were measured by the shake-flask method as previously reported by Wilson and Houle, 104, 105 and were found to be between log P 7.4 = ~2.2 – 2.8 which is in the appropriate range for brain entry. 90, 91, 93 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The octanol/aqueous buffer partition coefficients (log P 7.4 ) of [ 18 F] 26 - [ 18 F] 29 (Table 2) were measured by the shake-flask method as previously reported by Wilson and Houle, 104, 105 and were found to be between log P 7.4 = ~2.2 – 2.8 which is in the appropriate range for brain entry. 90, 91, 93 …”
Section: Resultsmentioning
confidence: 99%
“…Compounds [ 18 F] 1 and [ 123 I] 2 had limited aqueous solubility (20% EtOH in saline was required to dissolve the compounds), 80 and biological evaluation in rats showed very low brain uptake indicating that the compounds did not diffuse through the blood-brain barrier (BBB). 90-93 In vivo biodistribution studies with [ 76 Br] 3 in rats demonstrated brain penetrance, and in vitro autoradiography studies demonstrated specific binding. 82 Compounds [ 11 C] 6 , [ 11 C] 7 , and [ 11 C] 8 all penetrated the BBB of a baboon but did not display specific binding and were rapidly metabolized.…”
Section: Introductionmentioning
confidence: 99%
“…The f P value increased to 0.042 ± 0.003 ( n = 3) under the pre-blocked condition. These f P values are in the range expected for a radioligand with a measured logD value of 3.27 [41]. …”
Section: Resultsmentioning
confidence: 86%
“…Knowledge of logD, as an index of lipophilicity, is useful, for example, for benchmarking the lipophilicities of radiometabolites. The logD of [ 11 C]FIMX was determined essentially by a previously described technique [41] based on distribution of the radioligand between 1-octanol and sodium phosphate buffer (0.15 M; pH 7.4), but with a correction for radioligand instability because it was found that [ 11 C]FIMX degraded in the buffer to 79.1 ± 3.3% ( n = 4) of its original radiochemical purity over 57 min at room temperature (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation